A theory of regular Markov perfect equilibria in dynamic stochastic games: genericity, stability, and purification - Ulrich Doraszelski; Juan Escobar (Theoretical Economics, 2010)
This paper studies generic properties of Markov perfect equilibria in dynamic stochastic games. We show that almost all dynamic stochastic games have a finite number of locally isolated Markov perfect equilibria. These equilibria are essential and strongly stable. Moreover, they all admit purification. To establish these results, we introduce a notion of regularity for dynamic stochastic games and exploit a simple connection between normal form and dynamic stochastic games.
Keywords: C73; C61; C62; 330; Dynamic stochastic games; Markov perfect equilibrium; regularity; genericity; finiteness; strong stability; essentiality; purifiability; estimation; computation; repeated games